2018
DOI: 10.1371/journal.pone.0193568
|View full text |Cite
|
Sign up to set email alerts
|

Association between cognitive function and supplementation with omega-3 PUFAs and other nutrients in ≥ 75 years old patients: A randomized multicenter study

Abstract: A few studies have assessed the association between omega-3 polyunsaturated fatty acids (n-3 PUFA) and cognitive impairment (CI) in very old adults. The aim of this study was to evaluate the effect of a multinutrient supplementation rich in n-3 PUFA on the cognitive function in an institutionalized ≥75-year-old population without CI or with mild cognitive impairment (MCI). A multicenter placebo-controlled double-blind randomized trial was conducted between 2012 and 2013. Cognitive function was assessed at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…The study protocols, e.g., ( Mumme et al, 2019 ), multi-domain intervention studies, e.g., ( Lehtisalo et al, 2017 ; Rosenberg et al, 2018 ), the studies with different age range of seniors, e.g., ( Kita et al, 2018 ), the studies with cognitively impaired seniors, e.g., ( Baleztena et al, 2018 ; Mazza et al, 2018 ), and cross-over randomized control study ( Dodd et al, 2019 ), the review studies, e.g., ( Vauzour et al, 2017 ; Chen et al, 2019 ; Cremonini et al, 2019 ; Soldevila-Domenech et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study protocols, e.g., ( Mumme et al, 2019 ), multi-domain intervention studies, e.g., ( Lehtisalo et al, 2017 ; Rosenberg et al, 2018 ), the studies with different age range of seniors, e.g., ( Kita et al, 2018 ), the studies with cognitively impaired seniors, e.g., ( Baleztena et al, 2018 ; Mazza et al, 2018 ), and cross-over randomized control study ( Dodd et al, 2019 ), the review studies, e.g., ( Vauzour et al, 2017 ; Chen et al, 2019 ; Cremonini et al, 2019 ; Soldevila-Domenech et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…All the included RCT studies adhered to their aims and objectives of evaluating the benefits of DHA (and additional supplements) in ARCD, as described in their respective clinical trial registries. Majority of the studies concluded DHA supplementation (standalone or in combination) have no cognitive benefits in the elderly subjects [29,[31][32][33]25,26].…”
Section: Discussionmentioning
confidence: 99%
“…We explored, if higher doses of DHA supplementation altered the results by performing subgroup of studies, those supplemented ≥ 750 DHA / day [30,31,[24][25][26]. The results of subgroup analysis were similar to the primary results indicating no significant improvement with DHA supplementation.…”
Section: Effects On Subgroupsmentioning
confidence: 99%
“…Two distinct multi-nutrient formulations have failed to yield positive cognitive effects: one trial enrolled subjects that were normal or diagnosed with MCI 26 and another one patients with AD and normal baseline vitamin B12 and folate levels. 27 Other relatively large studies examined the effect of a patented formulation called Fortasyn Connect.…”
Section: Multi-nutrient Formulationsmentioning
confidence: 99%